MicroRNAs and metastases--the neuroblastoma link - Almeida, Maria I. (2010)
[Excerpt] MicroRNAs (miRNAs) are small noncoding RNAs of approximately 22 nucleotides in length that regulate gene expression post-transcriptionally. These small RNAs are fundamental regulators of several cellular processes, such as differentiation, development, apoptosis, proliferation, cell cycle regulation and metabolism, through the binding to 3' untranslated regions, coding sequence or 5' untranslated regions of target messenger RNAs (mRNAs), preventing their translation or causing their degradation.1 A modest change in only one miRNA will affect multiple mRNA targets; consequently, the deregulation of miRNAs has important consequences to the cellular homeostatic stability, and aberrant miRNAs expression patterns have been described in several types of cancer.2 Recently, miRNAs have been implicated in the metastatic process of several tumors such as human breast and colorectal cancers3 and, as reported this issue of Cancer Biology & Therapy by Guo et al. in neuroblastoma.4 These are extracranial solid tumors, arising from neural crest cells, that are most common in infants and children; metastasis, the main cause of death, is present at the time of diagnosis in approximately 60% of patients. (5) [...]